Implementación de un Prototipo de Cosecha de Agua para la Producción Sostenible en un Ecosistema Árido en la Parroquia Cangahua, Cantón Cayambe, Provincia de Pichincha. - Cunuhay López, Gissela Monserrate (2017)
Desertification occurs because of indirect factors, and the search sought to solve the scarcity of water resources, caused by various factors of an environmental nature that make the sustainability of natural resources impossible. The ecosystem was characterized environmentally in the Cangahua Parish in Cayambe Canton, a prototype of water using was defined to implement and determine the potential socio - environmental impact of the applied model. A decision matrix is applied to evaluate the feasibility of the three models of water harvesting management (waterboxx, air-drop and microreservorios). The waterboxx turned out to be the one of better applicability in the zone. It showed a significant water of saving, registering 60% with respect to a conventional drip irrigation under greenhouse conditions. The conventional irrigation for 28 days was consumed 201,6l in 32 plants, while with the waterboxx consumed 89,6l in the same time and for the same number of plants. The life of the waterboxx is 15 years which makes it economically viable.